Urgensi Perlindungan Identitas Anak Melalui Media Sosial - Setiawan, Setiawan; Fatmawati O, Nynda (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This study aims to examine the impact of children's development on the publication of their identities through social media and the application of Pasal 19 Undang-undang Sistem Peradilan Pidana Anak in the era of digitalization. Social media platforms such as Facebook, Instagram, and TikTok have become integral parts of daily life for children and adolescents, providing avenues for social interaction and exploration. However, with the increased use of social media, children also face serious risks to their privacy and identity. Threats include identity theft, cyberbullying, and exposure to harmful content. The discussion covers the psychological impacts of unsupervised social media use, such as social pressure and cyberbullying. Protecting children's identities through digital safety education and stringent regulatory implementation is crucial to creating a safe online environment that supports optimal child development, in accordance with the Child Protection Law in Indonesia.